Multifunctional Materials for Electro-Mechanical Applications: Synergistic Integration of Strength and Conductivity - Alok Kumar Tiwari (International Journal of Electro-Mechanics and Material Behaviour, 2025)
The integration of mechanical strength and electrical conductivity within a single material system has emerged as a critical requirement in the development of next-generation multifunctional materials. These materials are increasingly sought after in fields such as aerospace, flexible electronics, energy storage, and structural health monitoring, where the traditional separation of structural and functional materials leads to inefficiencies in weight, space, and overall performance. The convergence of these properties enables compact designs, reduced component count, and improved durability of systems exposed to mechanical and electrical stresses simultaneously. This review explores recent progress in the development of multifunctional materials that exhibit both high mechanical robustness and excellent electrical performance. Emphasis is placed on composite systems, particularly metal matrix composites, carbon-based nanomaterials, and conductive polymers, which have shown significant promise in achieving a balance between strength and conductivity. Strategies such as the incorporation of carbon nanotubes, graphene, metallic nanowires, and hybrid nanostructures are discussed in terms of their impact on the microstructural design, load transfer mechanisms, and conductive pathways. Additionally, the review highlights the fundamental challenges associated with combining these often-conflicting properties, including electron scattering at interfaces, filler agglomeration, and the trade-off between mechanical reinforcement and carrier mobility. Advances in nanotechnology, interface engineering, and hierarchical structuring are shown to play a pivotal role in addressing these challenges. Application areas such as wearable electronics, aerospace-grade structural components, and multifunctional batteries are used to illustrate the practical significance of these materials. Finally, the review outlines emerging trends, such as the use of machine learning in material discovery and the development of sustainable, recyclable composites. The paper concludes with perspectives on future research directions needed to fully realize the potential of multifunctional materials in real-world applications.
Keywords: Mechanical strength; Metal matrix composites; Multifunctional materials; conductive polymers; electrical conductivity; hybrid nanostructures